Functional genomics of dietary restriction and longevity in yeast. (April 2019) - Campos, Sergio E.; DeLuna, Alexander
Highlights: The replicative and chronological lifespans of yeast are models to investigate the mechanisms of longevity by dietary restriction. Available high-throughput screening tools enable functional-genomics views of aging and longevity in yeast. Recent unbiased screens have provided a comprehensive picture of the cellular mechanisms of longevity by dietary restriction. Systems-level views of longevity by dietary restriction underscore widespread cellular pathway crosstalk. Cell-cycle regulation and elements of the pheromone pathway emerge as mechanisms underlying chronological longevity in yeast. Abstract: Dietary restriction-limitation of calories or other specific nutrients in the diet-is the sole non-genetic intervention known to extend the lifespan of a wide range of model organisms from yeast to mammals. Cell biology studies on the responses to dietary restriction have provided important clues about the mechanisms of longevity; however, a comprehensive genome-wide description of lifespan by dietary restriction has been mostly absent. Large-scale genetic analysis in the budding yeast Saccharomyces cerevisiae offers a great opportunity to uncover the conserved systems-level mechanisms that give way to longevity in response to diet. Here, we review recent advances in high-throughput phenotyping of the replicative and chronological life spans of yeast cells, which have contributed to our understanding of longevity by dietary restriction and the cellular crosstalks of nutrient-sensing regulation.